Work-life balance measures, work-life balance, and organisational commitment - A structural analysis - Hendrik Godbersen; Susana Ruiz-Fernández; Marco Machura; Denise Elif Parlak; Christian Wirtz; Oliver A. Gansser (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2022)
Purpose: Our research aims to determine the impact of work-life balance on the components of organisational commitment in comparison to other key determinants and the influence of work-life balance measures on work-life balance. Methodology: We conducted two studies with 760 and 389 participants each. Our model, consisting of work-life balance measures, work-life balance, other working conditions, and organisational commitment is tested by structural equation modelling. Findings: Work-life balance positively influences the affective and normative component of organisational commitment. This influence, however, is weaker than the impact of other working conditions, like perceived leadership behaviour and the working climate. The only measure that has a significant impact on work-life balance is flexible working time. Practical implications: Our results imply that it is beneficial for organisations to improve their employees' work-life balance. Employers should, however, focus primarily on other working conditions when aiming to improve the organisational commitment of their employees. When launching work-life balance initiatives, organisations should focus on flexible working time arrangements. Originality: So far, it has not been sufficiently examined how a strong work-life balance impacts organisational commitment in comparison to other key determinants. Furthermore, most studies investigate the correlation between work-life balance measures and organisational commitment. We, on the other hand, propose a model in which work life-balance plays a mediating role between organisational measures and commitment and is analysed in comparison to other "regular" working conditions.
Keywords: 650